Legislative Framework for Decentralized Administration in Addressing River Pollution - Syaprillah, Aditia; Fuad Shehab Shyyab (Lembaga Contrarius Indonesia, 2025)
effectiveness, particularly concerning water pollution in river areas. This research examines the legislative framework for protecting river basins in Indonesia, focusing on water pollution. Using a normative legal research method with a conceptual approach, the study analyzes the current legislative provisions and their implementation. The findings reveal that while existing environmental protection laws and technical regulations for supervision and sanctions are in place, they have not been fully effective in preventing river pollution across various regions in Indonesia. The research suggests that a new legislative direction is necessary to support the successful implementation of environmental protection, advocating for sustainable and green legislation. It emphasizes the need for stronger administrative sanctions against individuals and corporations responsible for pollution and calls for enhanced oversight from national to local authorities. The study concludes that strengthening decentralized administration is crucial to ensuring that laws and regulations are correctly implemented, thereby addressing the persistent issue of river pollution and promoting long-term environmental sustainability.